Plasticity induced crack closure: a sensitivity analysis - Correia, L. (2013)
Plasticity induced crack closure (PICC) is closely linked to the monotonic and reversed plastic deformation occurring at the crack tip. The objective of the paper is to identify the different physical and numerical parameters affecting PICC, and develop a sensitivity analysis to quantify their relative importance. The main parameters affecting PICC are the load parameters, the yield stress, the size of finite elements and the numerical parameter considered to quantify PICC. The numerical predictions should be independent of numerical parameters, therefore further work is required to optimize the numerical models